Mutation analysis of the spike protein in Italian feline infectious peritonitis virus and feline enteric coronavirus sequences. (March 2021) - Decaro, N.; Mari, V.; Lanave, G.; Lorusso, E.; Lucente, M.S.; Desario, C.; Colaianni, M.L.; Elia, G.; Ferringo, F.; Alfano, F.; Buonavoglia, C.
Abstract: Feline coronavirus (FCoV) exists as two different genotypes, FCoV type I and II, each including two biotypes, feline enteric coronavirus (FECV) and feline infectious peritonitis virus (FIPV), the latter being a virulent variant originating from the former virus. Recently, two amino acid substitutions, M1058L and S1060A, within the spike protein have been associated to the FECV/FIPV virulence change. In this study, we have analysed the frequency of detection of such mutations in FIPV and FECV strains circulating in Italian cats and obtained information about their evolutionary relationships with reference isolates. A total of 40 FCoV strains, including 19 strains from effusions or tissue samples of FIP cats and 21 strains from faecal samples of non-FIP cats, were analysed. Mutation M1058L was detected in 16/18 FCoV-I and 1/1 FCoV-II strains associated with FIP, while change S1060A was presented by two FIPV strains. By phylogenetic analysis, FCoV sequences clustered according to the genotype but not according to the biotype, with FECV/FIPV strains recovered from the same animal being closely related. Further studies are needed to better define the genetic signatures associated with the FECV/FIPV virulence shift. Highlights: Spike protein sequences from FCoV strains circulating in Italian FIP ( n = 19) and non-FIP ( n = 21) cats were analysed. Mutations M1058L and S1060A were detected in 17 and 2 FCoV strains associated with FIP, respectively. By phylogenetic analysis, FCoV sequences clustered according to the genotype but not according to the pathotype. FECV/FIPV strains recovered from the same animal were closely related at the phylogenetic level. Further studies will better define the genetic signatures associated with the FCoV virulence shift.